Russia’s vision of the european green deal: insidious protectionism or opportunities for collaboration? - Ioana Mădălina MIRON (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The current paper provides an analysis of the European Green Deal on the territory of the Russian Federation. The development of relations between the European Union and Russia throughout the green transition has a significant impact on global prospects for deep decarbonization. This paper will demonstrate that the European Union cannot simply replace these imports with primary goods from other countries, and that Russia is not motivated to cut GHG emissions unless the European Union provides extra incentives. The current research emphasises the European Union and Russian Federation's common dependence on a carbon-intensive goods flows. Throughout this article, I will draw a parallel between the opportunities that the European Green Pact can offer to the Russian Federation's territory and the challenges that are perceived as a bad process for the economy and Russian exports. I will also present how essential this possibility for cooperation is for both governments, as well as the impact of the issues that have exacerbated the relationship between the EU and Russia, which has recently been brittle because of the causes of recent disputes.